ENGLISH ACADEMIC ACHIEVEMENT IN THE TOEFL ITP TEST: A COMPARATIVE GENDER ANALYSIS IN LEADING ISLAMIC PRIVATE HIGH SCHOOL - Ukhrowi, Wim (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2025)
English proficiency as a global competency is measured through the TOEFL ITP, while previous studies have reported gender disparities in language achievement. This study aims to examine the difference in TOEFL ITP scores between male and female students at a Private Pesantren-Based High School. This comparative quantitative research used a sample of 60 students (30 males, 30 females) selected through purposive sampling. TOEFL ITP score data were analyzed using descriptive statistics and an independent samples t-test. The results showed no significant difference between the scores of male (M=443.20, SD=31.55) and female (M=441.43, SD=28.06) students, with t(58)=0.229, p=0.820. Both groups significantly exceeded the minimum benchmark score of 400 (p<0.001). The findings indicate that the structured and disciplined pesantren environment potentially neutralizes gender differences in English achievement. The implication is that educational policies should focus on creating inclusive learning environments that minimize gender disparities in pesantren-based educational institutions.